Two new species of the genus Leeonychiurus Sun & Arbea, 2014 (Collembola: Onychiuridae) from Korea - Lee, Inae; Park, Kyung-Hwa (Zootaxa, 2017)
Two new species of the genus Leeonychiurus Sun & Arbea, 2014 from South Korea, i.e. L. koreanus sp. nov. and L. analis sp. nov., are described and illustrated. The former differs from other known congeners by having only 2 distinct pseudocelli on each side of Abd. III (three in all other species). The second species, L. analis sp. nov., being rather similar to L. koreanus sp. nov., can easily be distinguished due to the presence of dorsal pso on Th. I (absent in L. koreanus sp. nov.) and three dorsal pso on Abd. III (only two pso in L. koreanus sp. nov.), chaetotaxy of anal valves is also specific, characterized by the presence of chaetae a1 and the absence of chaeta c0 on upper anal valve. An identification key to all known species of the genus Leeonychiurus species is also provided.